Human muscle weakness and fatigue: the effects of disuse, age and exercise - White, Michael J. (1987)
Weakness and fatigue in the human triceps surae have been assessed objectively by the measurement of absolute force evoked using supramaximal stimulation. The effects of disuse, age and exercise were systematically investigated. Under control conditions the triceps surae of young men were found to generate high maximal tetanic forces, have a mean twitch time to peak tension of 107 msec and did not fatigue readily. This was indicative of a large muscle mass with a predominance of type I (slow twitch) fibres. Muscle temperature manipulation over the range 29.5 to 39.1°C did not affect maximal force generation but had a profound effect on the force and time course of twitch and unfused tetanic responses.